Mitochondrial Alterations in Nonalcoholic Fatty Liver Disease. Pediatric Case Description of Three Submitted Sequential Biopsies - Da Silva, Gustavo Henrique; Coelho, Kunie Iabuki Rabello [UNESP]; Rabello Coelho, Claudio Antonio [UNESP]; Fazzio Escanhoela, Cecilia Amelia (Medical Univ Press, 2009)
Nonalcoholic fatty liver disease (NAFLD) is a clinical-pathological syndrome that encompasses a wide spectrum of morphologic alterations, ranging from simple hepatic steatosis to a more severe stage, known as nonalcoholic steatohepatitis (NASH). The purpose of this clinical report was to contribute to the understanding of mitochondrial alterations in NAFLD. The child (13-month-old) underwent initial biopsy in the year 2000 and was diagnosed with diffuse macro and microvesicular steatosis. Two additional biopsies were performed in 2001 and 2004. A high percentage of microvesicular steatosis was observed in the biopsies performed in 2000 and 2001. Mitochondrial size was slightly increased in the biopsy performed in the year 2000, significantly increased in 2001 and decreased in 2004. The presence of "mitochondrial hypertrophy" in the hepatocytes of an asymptomatic pediatric patient whose disease presentation was typical of NAFLD, excluding other pathological processes, allowed us to suspect that such a defect was considered the primary mitochondrial disorder.
Keywords: NAFLD; microvesicular steatosis; mitochondrial alterations; liver